Dongeng Boneka sebagai Media Edukasi: Implementasi Modul Pencegahan Kekerasan Seksual oleh Kakak Aman Indonesia di SDN Kaloran Kidul Kota Serang - Zidan, Muhammad; Siregar, Herlina; Pertiwi, Fitri; Maysara, Siska Resti (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This The issue of sexual violence against children remains a serious and often overlooked challenge, particularly at the elementary school level. Prevention efforts must be carried out through educational and communicative approaches, tailored to the psychological developmental stages of children. This community service activity aims to implement a sexual violence prevention module developed by the Kakak Aman Indonesia organization, utilizing puppet storytelling as the main medium at SDN Kaloran Kidul, Serang. The implementation process included storytelling sessions, presentations on sexual education—such as understanding private body parts that should not be touched by others and what to do when experiencing sexual violence or harassment—singing educational songs about sexual violence which were specifically adapted by Kakak Aman Indonesia), and was concluded with interactive games. The use of puppet storytelling was chosen due to its narrative and visual strengths, which are effective in capturing children's interest while delivering self-protection messages in a gentle yet impactful way. Based on the results, students showed increased understanding of personal body boundaries, the importance of saying “no” to inappropriate touches, and the ability to recognize risky or unsafe situations. Teachers also responded positively, recognizing the media as a fun and value-rich learning tool.These findings suggest that puppet storytelling is an effective, child-friendly, and easily applicable medium in efforts to prevent sexual violence. Through a simple yet meaningful approach, this method creates a safe and enjoyable space for children to learn how to protect themselves. This small effort is hoped to be a starting point toward the realization of a school environment that is more aware, caring, and free from violence.